Temple Sources in Ancient Iraq from the Era of Dawn of Dynasties until the Fall of Babylon (2880-539 BC) - Jawad Nassar , Researcher. Maha; Shamkhi Jaber, Prof. Dr. Iman (Basra studies journal, 2023)
The old temple of Iraq is considered a religious and economic institution in some historical periods, especially during the dawn of dynasties. Economic resources began to be overwhelmed by the general public and kings in order to please the gods and approach them with the support of the political class at the time. The temple owned land, agricultural fields, warehouses, and workplaces. This power quickly dissipated, deviated, and economic powers were withdrawn, and the temple performed only the religious function. This is due to the policy of rulers and kings who removed the power of the temple for fear of its growing power so as not exceeding the authority of the state by separating religion from politics and withdrawing some of their privileges.